1991
DOI: 10.1520/jfs13117j
|View full text |Cite
|
Sign up to set email alerts
|

Gunshot Residue Particles Formed by Using Different Types of Ammunition in the Same Firearm

Abstract: Examples of some exceptional compositions of gunshot residue particles, formed by using different types of ammunition in the same firearm, are presented. The composition that may be encountered in casework may differ appreciably from the “classic” criteria for identification of gunshot residues. This fact must therefore be taken into account by the expert when interpreting case results, and thus, every case has to be dealt with on an individual basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 8 publications
1
20
0
2
Order By: Relevance
“…Several studies [17,18,19] have reported the formation of "mixed composition" GSR particles when different ammunition is fired from the same firearm (Figs. 2 and 3).…”
Section: Compositions Classification and Interpretationmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies [17,18,19] have reported the formation of "mixed composition" GSR particles when different ammunition is fired from the same firearm (Figs. 2 and 3).…”
Section: Compositions Classification and Interpretationmentioning
confidence: 99%
“…If such ammunition is involved in a shooting case much better association can be achieved. The degree of association can be increased further if mixed GSR compositions [17,18,19] can be found in the exhibits compared.…”
Section: Gsr Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The types of firearms and varieties of ammunition used are listed in Tables 1 and 2. The barrels, chambers, bolts and magazines were cleaned carefully with hot soapy water and pure benzine prior to the experiments in order to remove potential impurities from previous shooting [14] and to avoid smearing of gun oils [4,13], which -based on our own findings -may produce rhodizonate-positive precipitates due to additives containing heavy metals. Subsequently, prior to firing on the skin samples, three shots were fired into the backstop in order to assure that the barrels were coated with smoke and powder residues for the whole series of shots into the samples.…”
Section: Materials (Weapons and Ammunition)mentioning
confidence: 99%
“…Farklı markalarda fişeklerin kapsül bileşim-leri de farklılık gösterebilmekte ve bunların artıkları da farklı maddelerden oluşmaktadır. Dolayısıyla artık ların incelenmesi yoluyla kullanılan merminin marka sı hakkında fikir sahibi olunabilir (46). Bakır yönün den zengin gömlekli mermilerde atış artıklarında kay da değer miktarda bakıra rastlanmıştır (47).…”
Section: Atiş Artiklarinin Sem/ Eds İle İncelenmesi̇unclassified